Pengaruh Stigma Seksual Terhadap Ideasi Bunuh Diri pada Individu Lesbian Gay Bisexual Transgender (LGBT) Dewasa Awal - Jihan Haniifa Azhari; Dian Kartika Amelia Arbi (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to examine the influence of sexual stigma on suicidal ideation in early adult lesbian, gay, bisexual, and transgender (LGBT) individuals aged 18-29 in Indonesia. Suicidal ideation is a global mental health issue frequently experienced by LGBT individuals due to discrimination and stigma. The study employed a quantitative survey design, involving 120 LGBT early adult participants selected through purposive sampling. The research instruments included an adapted version of the Sexual Stigma Scale to measure sexual stigma and the Adult Suicidal Ideation Questionnaire (ASIQ) to measure suicidal ideation. Data analysis utilized linear regression to assess the influence of sexual stigma on suicidal ideation. The results revealed a significant positive relationship between sexual stigma and suicidal ideation, with a Pearson correlation coefficient of 0.414 (moderate category) and a significance value of 0.000 (p < 0.01). Sexual stigma contributed 17.1% to suicidal ideation, indicating a significant influence while acknowledging the presence of other influencing factors. These findings emphasize that higher sexual stigma is associated with an increased risk of suicidal ideation in LGBT individuals..